Abu Bakar Bashir's imprisonment : what next? - Muhammad Haniff Hassan (2012)
The conviction of Abu Bakar Bashir is an important milestone in the fight against violent radicals in Indonesia. However, its effect on the radicalisation problem on the ground may not be significant unless Bashir’s influence within and outside the prison is curbed.